African hermeneutics - Mburu, Elizabeth W. 1968- (Carlisle, United Kingdom HippoBooks, 2019)
Part I.General principles of hermeneutics.Introduction --The African worldview : theological aspects --The African worldview : philosophical aspects --An African hermeneutic : a four-legged stool --Part II.Specific principles of hermeneutics.Understanding the context of the Bible --Interpreting stories --Interpreting wisdom --Interpreting songs --Interpreting letters --Conclusion.
"Interpretation of Scripture occurs within one's worldview and culture, which enhances our understanding and ability to apply Scripture in the world. However, few books address Bible interpretation from an African perspective and no other textbook uses the intercultural approach found here. This book brings both an awareness of how one's African context gives a lens to hermeneutics, but also how to interpret texts with integrity despite our cultural influences." --
Includes bibliographical references (pages 217-223) and index
Keywords: Bible -- Hermeneutics; Bible; Philosophy, African; Hermeneutics; Religion; Church History; Africa -- Church history; Africa -- Religion; Africa